2010
DOI: 10.1111/j.1447-0594.2010.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide of elderly persons: Towards a framework for prevention

Abstract: Suicide is an act of intentionally terminating one's own life. Although suicide rates vary across demographic categories, they have increased by approximately 60% in the last 50 years. Many studies of adolescent suicidal behavior have noted impulsivity to be a common feature in the younger age group, while with older people there is evidence of planning and a strong intent to die. In fact, older people are most successful as an age group with approximately one in four attempts resulting in death. While very co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…According to data of United Nations (UN), suicide is found among the ten main causes of death in the world for individuals of all ages, thus being a relevant health care problem 1 . Studies made in several countries have shown that rates of suicide attempts are frequently high and provide evidence that this fact is continuously underestimated [2][3][4] . The causes relate particularly to social factors like unemployment 5 and illnesses as depression 6 and schizophrenia [2][3][4] .…”
Section: Introductionmentioning
confidence: 98%
“…According to data of United Nations (UN), suicide is found among the ten main causes of death in the world for individuals of all ages, thus being a relevant health care problem 1 . Studies made in several countries have shown that rates of suicide attempts are frequently high and provide evidence that this fact is continuously underestimated [2][3][4] . The causes relate particularly to social factors like unemployment 5 and illnesses as depression 6 and schizophrenia [2][3][4] .…”
Section: Introductionmentioning
confidence: 98%
“…Literatürde tamamlanmış intiharlarda en sık kullanılan yöntemlerin ası, ateşli silah ve kimyasal maddelerin olduğu bildirilmiştir (2,8,9). TUİK verilerine göre ülkemizde intihar yöntemleri bölgelere ve cinsiyete göre kısmi farklılık göstermekle birlikte en sık ası yöntemi kullanıldığı belirlenmiştir.…”
Section: Resim 2 Ası Eyleminin Gerçekleştiği Yerunclassified
“…The risk factors associated with suicide in older adults are mixed and varied. Most common are intentional self-harm with previous histories of suicide attempts [9,[17][18][19], chronic pain [1], physical illness [20][21][22][23], functional impairment [23,24], loss of a partner or a significant other [25,26], alcoholism [27], loneliness or hopelessness [20,21], depression [17,20,[28][29][30][31], economic dependency [1], remoteness [32] and social isolation [17,20,21]. These suicide risk factors either individually or collectively can affect older adults, but in most of the scenarios recorded globally, it was discovered that the integration of several suicide risk factors influences late-life crisis [20].…”
Section: Introductionmentioning
confidence: 99%